Biofilm-induced changes to the composite surface. (August 2017) - Nedeljkovic, Ivana; De Munck, Jan; Ungureanu, Andreea-Alexandra; Slomka, Vera; Bartic, Carmen; Vananroye, Anja; Clasen, Christian; Teughels, Wim; Van Meerbeek, Bart; Van Landuyt, Kirsten L.
Abstract: Objectives: Composites may undergo biodegradation in the oral cavity. The objective was to investigate the effect of single- and multi-species biofilms on the surface roughness and topography of two composites. Methods: Disk-shaped specimens of a paste-like, Bis-GMA-free (Gradia Direct Anterior, GC), and a flowable, Bis-GMA-based composite (Tetric EvoFlow, Ivoclar-Vivadent) were prepared. After ethylene-oxide sterilization (38 °C), specimens (n = 3) were incubated with Streptococcus mutans or mixed bacterial culture ( Streptococcus mutans, Streptococcus sanguinis, Actinomyces naeslundii and Fusobacterium nucleatum ). As negative controls, unexposed specimens and specimens exposed to sterile medium (BHI) were used. Specimens exposed to acidified BHI medium (pH = 5) and enzymatic solution of cholesterol esterase served as positive control. Following 6-week incubation, the attached biofilms were collected for real-time PCR assessment, after which the surface roughness and topography of the specimens were analyzed with atomic force microscopy. Surface hydrophilicity/hydrophobicity was determined by contact angle measurements. Biofilm structure was analyzed with scanning electron microscopy. Results: Even though multi-species biofilms were thicker, with more cells attached, they did not significantly affect the surface roughness of the composites. On the other hand, S. mutans alone significantly increased the roughness of Tetric by 40.3%, while its effect on Gradia was lower (12%). The total amount of attached bacteria, however, did not differ between the composites. Conclusions: S. mutans can increase the surface roughness of composites, depending on their composition. This ability of S. mutans is, however, mitigated in co-culture with other species. In particular, bacterial esterases seem to be responsible for the increased composite surface roughness upon biofilms exposure. Clinical significance: Cariogenic bacteria can degrade composites, thereby increasing the surface roughness. Increased roughness and subsequent improved bacterial accumulation may facilitate the development of secondary caries around composites, which is the most common reason for the restoration failure.